1996
DOI: 10.1089/jir.1996.16.941
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Nonspecific Immunity of Human Placenta at Term: Possible Role of Endogenous Tumor Necrosis Factors and Interferons

Abstract: The antiviral immunity of human placenta and amniotic membrane in an organ culture (OC) system was studied. Freshly isolated explants of most of the placentas at term and the amniotic membranes were found to be relatively resistant to herpes simplex virus type 1 (HSV-1), encephalomyocarditis virus (EMCV), and vesicular stomatitis virus (VSV) infections. After in vitro aging, however, the OC acquired the sensitivity to the viruses. In about 66%-90% of placentas, resistance of freshly isolated explants to the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 12 publications
0
21
0
Order By: Relevance
“…Alteration of HLA-G or locus-specific class I gene expression may also interfere in the balance between escape from cytotoxic T lymphocytes and maintenance of protection from NK cells (16 -19, 57). Given that IFN-␤ is produced in virally infected trophoblast and amnion (58,59), specific pathways of HLA-G modulation could permit infected cells to block NK and T-cell responses, as seen during maternal-fetal transmission of human cytomegalovirus (60) or human immunodeficiency virus. Alternatively, lysis of infected material could be triggered by CD94/NKG2C receptors through HLA-E surface expression or by HLA-G-restricted T-cell Receptor and thus prevent pathogen spreading from the placental cells to the fetus.…”
Section: Figmentioning
confidence: 99%
“…Alteration of HLA-G or locus-specific class I gene expression may also interfere in the balance between escape from cytotoxic T lymphocytes and maintenance of protection from NK cells (16 -19, 57). Given that IFN-␤ is produced in virally infected trophoblast and amnion (58,59), specific pathways of HLA-G modulation could permit infected cells to block NK and T-cell responses, as seen during maternal-fetal transmission of human cytomegalovirus (60) or human immunodeficiency virus. Alternatively, lysis of infected material could be triggered by CD94/NKG2C receptors through HLA-E surface expression or by HLA-G-restricted T-cell Receptor and thus prevent pathogen spreading from the placental cells to the fetus.…”
Section: Figmentioning
confidence: 99%
“…Thus within the context of the broad scope of IFN effects, it seems plausible that pregnancy-associated IFNs may also participate in protection of the fetus against vertically transmitted viruses. Support for such a notion has been provided by experiments with vesicular stomatitis virus (VSV) in vitro [Paradowska et al, 1996] and by a population study of intrauterine herpes simples virus (HSV) infection [Zdravkovic et al, 1997].…”
Section: Introductionmentioning
confidence: 99%
“…The resistance of murine macrophages and Kupffer cells to HSV infection has been known much earlier [4][5][6][7]. We found that the resistance is present not only in macrophages, but also in other cells ex vivo, and that is not directed against HSV only, but also against viruses belonging to different taxonomic groups such as encephalomyocarditis virus (EMCV, Picornaviridae), and vesicular stomatitis virus (VSV, Rhabdoviridae) [8][9][10][11]. The resistance of freshly isolated human peripheral blood leukocytes to viral infection was a good reason for elaboration the test for measuring the degree of innate immunity [8].…”
Section: Introductionmentioning
confidence: 82%
“…Our results showed that kinetics of VSV replication in freshly isolated human peripheral blood leukocytes (PBL) indicates degree of the resistance to viral infection. The lack of VSV replication in the cells (0-1 log TCID50) indicates complete resistance, low level of VSV replication (2-3 log) partial resistance, and high VSV titer (more than 4 log) very low or lack of the resistance [9].…”
Section: Introductionmentioning
confidence: 99%